Analysis of Comparative Advantage Strategy Implementation on The Customer Loyalty of BRI Sharia in DIY - Awis Hardjito (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2015)
Competition occurs among Islamic banks increasingly tight. In order to survive and remain competitive, an Islamic bank should have an identity and uniqueness which differentiates with other Islamic banks. BRI Sharia in order to enter the world of competition and survive should implement strategies remain competitive advantages to maintain the loyalty of its customers. These strategies are divided into cost leadership, differentiation and focus. The expectation by applying one of these strategies, BRI Sharia can retain the loyalty of the customers and gain new customers. This research aimed to determine which strategies are applied by BRI Sharia. The strategies of the competitive advantage created by M. Porter's such as cost leadership, differentiation, and focus affect significantly on customer loyalty. Data processing was performed using SEM analysis (Structural Equation Model). The results showed that customer loyalty variation can be explained by variabel s of cost leadership, differentiation and focus strategies. From the test results we can conclude that only cost leadership strategy variable that significantly affect customer loyalty of BRI Sharia.